2023
DOI: 10.1021/acs.joc.3c00672
|View full text |Cite
|
Sign up to set email alerts
|

Surmounting Byproduct Inhibition in an Intermolecular Catalytic Asymmetric Alkene Bromoesterification Reaction as Revealed by Kinetic Profiling

Abstract: Kinetic profiling has shown that a (DHQD) 2 PHALcatalyzed intermolecular asymmetric alkene bromoesterification reaction is inhibited by primary amides, imides, hydantoins, and secondary cyclic amides, which are byproducts of common stoichiometric bromenium ion sources. Two approaches to resolving the inhibition are presented, enabling the (DHQD) 2 PHAL loading to be dropped from 10 to 1 mol % while maintaining high bromoester conversions in 8 h or less. Iterative post-reaction recrystallizations enabled a homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Following from this, auto-VTNA was applied to kinetic data from 22 publications, including stoichiometric and catalytic reactions (Table 4, entries 1-14) containing up to 6 reaction species (reactants, reagents, catalyst and additives). 5,8,9,34,[37][38][39][40][41][42][43][44][45][46] The current approach to VTNA experimentation involves performing a "standard" reaction, under synthetically relevant conditions, followed by "different excess" experiments, where only the initial concentration of each reaction species is altered.…”
Section: Automatic Determination Of Rate Equations Using Auto-vtnamentioning
confidence: 99%
See 1 more Smart Citation
“…Following from this, auto-VTNA was applied to kinetic data from 22 publications, including stoichiometric and catalytic reactions (Table 4, entries 1-14) containing up to 6 reaction species (reactants, reagents, catalyst and additives). 5,8,9,34,[37][38][39][40][41][42][43][44][45][46] The current approach to VTNA experimentation involves performing a "standard" reaction, under synthetically relevant conditions, followed by "different excess" experiments, where only the initial concentration of each reaction species is altered.…”
Section: Automatic Determination Of Rate Equations Using Auto-vtnamentioning
confidence: 99%
“…This was performed for kinetic data obtained from 15 publications. 5,8,9,34,[37][38][39][40][41][42][43][44][45][47][48][49][50] Two of these publications were omitted as sequential VTNA had revealed that reaction orders change with the initial concentrations of reactants. 38,50 Kinetic data from the remaining 13 publications was re-analysed by Auto-VTNA sequentially (Table SX) and by automatic total VTNA (Table 2).…”
Section: Automatic Determination Of Rate Equations Using Auto-vtnamentioning
confidence: 99%